2013
DOI: 10.5235/20504721.1.2.268
|View full text |Cite
|
Sign up to set email alerts
|

Family violence, fathers, and restoring personhood

Abstract: Consultation on fatherhood in North Carolina was provided by Deric Boston.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…If safety issues clearly exist for children and victims of domestic violence, caseworkers should identify other options for involving the offenders without physical presences in family meetings, such as holding a separate meeting for offenders and victims (Olson, ). It is also necessary to help domestic violence offenders obtain safe and caring ways of relating to their families so that they can participate more actively in family meetings without serious safety concerns (Pennell, Sanders, Rikard, Shepherd, & Starsoneck, ). We also suggest that future researchers should explore whether team facilitators have sufficient preparation time and resources to safeguard victims and engage offenders appropriately within family meetings when domestic violence is identified.…”
Section: Discussionmentioning
confidence: 99%
“…If safety issues clearly exist for children and victims of domestic violence, caseworkers should identify other options for involving the offenders without physical presences in family meetings, such as holding a separate meeting for offenders and victims (Olson, ). It is also necessary to help domestic violence offenders obtain safe and caring ways of relating to their families so that they can participate more actively in family meetings without serious safety concerns (Pennell, Sanders, Rikard, Shepherd, & Starsoneck, ). We also suggest that future researchers should explore whether team facilitators have sufficient preparation time and resources to safeguard victims and engage offenders appropriately within family meetings when domestic violence is identified.…”
Section: Discussionmentioning
confidence: 99%
“…Research has found age to be associated with attrition, with younger men being more likely to drop out of treatment than older men (Bowen & Gilchrist, 2006;Brodeur et al, 2008;Cadsky et al, 1996;Gover et al, 2011;Rooney & Hanson, 2001;Pennell et al, 2013;Scott, 2004). This is supported by a meta-analysis that found that across family violence treatment programmes, completers and non-completers differed based on age, with older men being 16% more likely to complete treatment (Jewell & Wormith, 2010).…”
Section: Agementioning
confidence: 94%
“…It has been found that some single fathers drift from their children shortly after birth and have little involvement in their lives (Cowan et al, 2010). Family violence programme participants report that a common motivation for completing treatment is a desire to be a better father to their children (Pennell et al, 2013). Therefore, men who are not involved in their children's lives may be less likely to have this motivation for programme completion.…”
Section: Relationship Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…However, limited research has been conducted in this area. One motivation that has been discussed in literature is the desire to be a better father (Pennell et al, 2013). Men who completed the programme described wanting to spend more time with their children, and be better role models by interacting with their children and partners in a non-confrontational manner (Pennell et al, 2013).…”
Section: Motivationmentioning
confidence: 99%